Studying the Digital Society: Digital Methods between Tradition and Innovation in Social Research - Addeo, Felice; Masullo, Giuseppe (Italian Sociological Review, 2021)
Contemporary societies are facing progressive and swirling transformation due to the digital and technological innovations and their application to social facts and actions. These dynamics are changing the structure, the practices, the symbols and the shared meanings of our societies so progressively and deeply that many scholars to refer to our current social organizations as Digital Society. Digital Society has distinctive and unprecedented features, as for the first time these characteristics are eminently and intensely communicative. They require the development and the implementations of interpretative schemes and methodological solutions better suited to understand the current complexity. Some authors go further by arguing for a new scientific paradigm for social research. Yet, Digital Society is a research object whose operational definition has not been formulated in a definitive and shared way by social scientists. Moreover, the flourishing of online social and communicative practices and new social networks, the innovative ways to frame into data the online activities of individuals make the knowledge drawn from the Web always uncertain and at high risk of a rapid obsolescence. Social Research tried to face the challenges posed by the Digital Society first by adapting its methods to the online practices and interactions, then by creating new methods in order to analyze those online experiences that could not be framed using the traditional social research tools.